DESIGN OF PARKING INFORMATION SYSTEM OF LABUHANBATU UNIVERSITY WE-BASED WATERFALL METHOD - Ela Juliana Manurung; Ibnu Rasyid Munthe; Elysa Rohayani Hasibuan (Jurnal Mantik, 2022)
The rapid advancement of technology and the demands of information progress and the improvement of human life quality. With the rapid advancement of technology, productivity and work efficiency have increased. With so many companies utilizing increasing technology for productivity, one of them is that, because of the many drivers who park in the Parkir Place of Labuhanbatu University, technology is needed that can increase the effectiveness and efficiency of work in collecting motor vehicle data. This built application was created using tools such as VSC, MySQL, and XAMPP as a database with HTML and PHP programming languages and designed with simple flow and interface design using design methods including context diagram design, data flow diagram, database table structure, and other designs that explain the running flow of parking management applications at Labuhanbatu University Based WEB, so that it can be used easily by employees in speeding up time and analyzing energy.